The complete mitochondria genome of Chrysomya phaonis (Seguy, 1928) (Diptera: Calliphoridae). Issue 1 (1st January 2016) - Chen, Jian; Qiu, Deyi; Yue, Qiaoyun; Wang, Chuanxian; Li, Xiaohong
Abstract: Chrysomya phaonis (Seguy, 1928) is one of the blowflies of great medical and forensic importance. In this paper, we report that the entire genome of mitochondrial DNA of C. phaonis is 15, 831 bp in length, which consists of 39 genes including13 protein-coding genes, 24 tRNA genes, 2 mitochondrial ribosomal RNA genes, and a 992 bp non-coding A + T-rich region. The overall base compositions of A, G, C, and T are 38.79%, 9.75%, 14.15%, and 37.31%, respectively. We provide the first complete mitochondrial genome of C. phaonis, and should provide useful information for phylogenetic and species identification for C. phaonis .